PENGARUH PUPUK KASCING DAN NPK 16:16:16 TERHADAP PERTUMBUHAN SERTA PRODUKSI TANAMAN GAMBAS (Luffa acutangula) - Andri Kusnawan; Maizar (UIR Press, 2025)
This research aimed to determine the interaction and main effects of vermicompost fertilizer and NPK 16:16:16 on the growth and production of gambas plants. It was conducted at the Experimental Farm of the Faculty of Agriculture, Riau Islamic University, Pekanbaru, from February to May 2023. The research used a Completely Randomized Factorial Design consisting of two factors. The first factor is the dose of vermicompost fertilizer (K), which consists of 4 levels, namely 0, 540, 1,080, and 1,620 g per plot, and the second factor is the dose of NPK 16:16:16 (N) fertilizer, which consists of 4 levels, namely 0, 10, 20, and 30 g per plant. The parameters observed were the number of leaves, flowering age, harvest age, number of fruits per plot, fruit weight per plot, fruit weight per fruit, and number of remaining fruits per plot. The observation data were statistically analyzed, and a further BNJ test was conducted at the 5% level. The results showed that the interaction effect of vermicompost fertilizer and NPK 16:16:16 was significant for the parameters number of leaves, number of fruits per plot, weight of fruit per plot, weight of fruit per fruit, and number of remaining fruits per plot. The best treatment was at a vermicompost dose of 1,620 g per plot and NPK 16:16:16 30 g per plant. The main effect of vermicompost fertilizer was significant on all observation parameters. The best treatment was at a dose of 1,620 g per plot. The main effect of NPK 16:16:16 was significant on all observation parameters. The best treatment was 30 g per plant